2002
DOI: 10.1152/jn.00438.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interneuronal and Peptidergic Control of Motor Pattern Switching inAplysia

Abstract: It has been proposed that a choice of specific behaviors can be mediated either by activation of behavior-specific higher order neurons or by distinct combinations of such neurons in different behaviors. We examined the role that two higher order neurons, CBI-2 and CBI-3, play in the selection of motor programs that correspond to ingestion and egestion, two stimulus-dependent behaviors that are generated by a single central pattern generator (CPG) of Aplysia. We found that CBI-2 could evoke either ingestive, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
247
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(258 citation statements)
references
References 63 publications
(59 reference statements)
9
247
0
2
Order By: Relevance
“…We used a system-oriented strategy that allowed us to identify and characterize a family of neuropeptides that induce rhythmic feeding motor output in Aplysia. This strategy took advantage of the fact that the CBCs fulfill a critical role in feeding behavior and that CBCs contain neuropeptides that act on the feeding circuitry (Sossin et al, 1987;Lloyd, 1989;Xin et al, 1999;Morgan et al, 2000Morgan et al, , 2002Jing and Weiss, 2001). MALDI analysis of the cut ends of the CBCs revealed a number of peaks, some of which are likely to represent novel peptides.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We used a system-oriented strategy that allowed us to identify and characterize a family of neuropeptides that induce rhythmic feeding motor output in Aplysia. This strategy took advantage of the fact that the CBCs fulfill a critical role in feeding behavior and that CBCs contain neuropeptides that act on the feeding circuitry (Sossin et al, 1987;Lloyd, 1989;Xin et al, 1999;Morgan et al, 2000Morgan et al, , 2002Jing and Weiss, 2001). MALDI analysis of the cut ends of the CBCs revealed a number of peaks, some of which are likely to represent novel peptides.…”
Section: Discussionmentioning
confidence: 99%
“…FCAPs-initiated buccal motor programs could be ingestive, egestive, or intermediate. Previous work has shown that neuropeptide APGWamide can bias motor programs toward ingestion Morgan et al, 2002), and neuropeptide ANPY can bias motor programs toward egestion (Kupfermann et al, 2001). Importantly, in contrast to the FCAPs, APGWamide and ANPY do not initiate motor programs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations